Barakah – How can we obtain blessings in Ramadan? - Seise, Claudia (Azizah) (aboutislam.net, 2018)
We know that Ramadan is a month full with barakah or blessings. For every obligatory act of worship, we are being rewarded seventy times more than in any other time of the year.